1987
DOI: 10.1128/mcb.7.1.314
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of spacer sequences flanking the rat 45S ribosomal DNA gene.

Abstract: The transcriptional activity of spacer sequences flanking the rat 45S ribosomal DNA (rDNA) gene were studied. Nascent RNA labeled in in vitro nuclear run-on reactions hybridized with both 5' and 3' spacer regions. The highest level of hybridization was seen with an rDNA fragment containing tandem repeats of a 130-base-pair sequence upstream of the 45S rRNA initiation site. Synthesis of RNA transcripts homologous to this internally repetitious spacer region was insensitive to high levels of a-amanitin, suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…This is certainly its major effect in our assays, and it is also likely to be quite significant in vivo on the endogenous mammalian rRNA genes because polymerases clearly do approach the initiation region from upstream. These spacer polymerases include ones that initiated at promoters in the rDNA spacer (Cassidy et al 1987;Harrington and Chikaraishi 1987;Kuhn and Grummt 1987;Tower et al 1989) and possibly also ones that failed to terminate at the 3' end of the previous tandem rRNA gene. A terminator element could, however, have other positive effects on transcription as well.…”
Section: Discussionmentioning
confidence: 99%
“…This is certainly its major effect in our assays, and it is also likely to be quite significant in vivo on the endogenous mammalian rRNA genes because polymerases clearly do approach the initiation region from upstream. These spacer polymerases include ones that initiated at promoters in the rDNA spacer (Cassidy et al 1987;Harrington and Chikaraishi 1987;Kuhn and Grummt 1987;Tower et al 1989) and possibly also ones that failed to terminate at the 3' end of the previous tandem rRNA gene. A terminator element could, however, have other positive effects on transcription as well.…”
Section: Discussionmentioning
confidence: 99%
“…While mouse rDNA evidently does not contain spacer promoters within -1. 8 kilobase pairs (kbp) upstream from the gene promoter (46), nuclear run-on transcription data (15) in conjunction with in vitro runoff transcription data (13) suggest that an initiation site might exist within the adjoining several-hundred-basepair region. Furthermore, the identification of transcriptional terminators immediately upstream of mammalian gene promoters (13,16) has also indicated that transcripts read toward the gene promoter from the spacer.…”
mentioning
confidence: 99%
“…This result was surprising for at least two reasons. First, although it is now recognized that NTS sequences are transcribed in some organisms (9,23,25,35,36), those transcripts appear to be very unstable and have not been found to accumulate in cells to any appreciable extent. Second, the relationship between the relative abundance of NTS transcripts and the functional state of mitochondria or the mitochondrial genome was not immediately obvious.…”
mentioning
confidence: 99%